2009
DOI: 10.1007/s11064-009-0105-7
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Kinase Inhibitor AG126 Reduces 7-Ketocholesterol-Induced Cell Death by Suppressing Mitochondria-Mediated Apoptotic Process

Abstract: The preventive effect of tyrosine kinase inhibitor AG126 against the 7-ketocholesterol toxicity was investigated in relation to the mitochondria-mediated cell death process. 7-Ketocholesterol induced the nuclear damage, the mitochondrial membrane permeability changes, the formation of reactive oxygen species and the depletion of GSH, which leads to cell death in differentiated PC12 cells. Tyrphostin AG126 significantly attenuated the 7-ketocholesterol-induced decrease in cytosolic Bid and Bcl-2 levels, increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…7β-OH causes re-arrangement of the liquid-ordered phase which results in the formation of lipid rafts (Wang et al, 2008; Mitomo et al, 2009); it is also a potent inhibitor of α protein kinase C, an enzyme critical for memory consolidation and synaptic plasticity that is implicated in AD (Nelson and Alkon, 2005). Another oxysterol that might derive from the autoxidation of cellular cholesterol released during neurodegeneration is 7α-OH, which appeared to be responsible for SH-SY5Y cell death (Kölsch et al, 2000); a further possibility is 7-K. 7-K has been shown to enhance mitochondrial dysfunction in the neuronal PC12 cell line, leading to cell death (Kim et al, 2006; Kim and Lee, 2010; Jang and Lee, 2011). It has also been reported that incorporation of 7-K to lipid raft domains of plasma membranes triggers apoptotic signaling; α-tochopherol (vitamin E) reduces the cytotoxicity of 7-K by inhibiting its distribution to the lipid raft domains (Berthier et al, 2004; Royer et al, 2009).…”
Section: The Involvement Of Oxysterols In Ad Pathogenesismentioning
confidence: 99%
“…7β-OH causes re-arrangement of the liquid-ordered phase which results in the formation of lipid rafts (Wang et al, 2008; Mitomo et al, 2009); it is also a potent inhibitor of α protein kinase C, an enzyme critical for memory consolidation and synaptic plasticity that is implicated in AD (Nelson and Alkon, 2005). Another oxysterol that might derive from the autoxidation of cellular cholesterol released during neurodegeneration is 7α-OH, which appeared to be responsible for SH-SY5Y cell death (Kölsch et al, 2000); a further possibility is 7-K. 7-K has been shown to enhance mitochondrial dysfunction in the neuronal PC12 cell line, leading to cell death (Kim et al, 2006; Kim and Lee, 2010; Jang and Lee, 2011). It has also been reported that incorporation of 7-K to lipid raft domains of plasma membranes triggers apoptotic signaling; α-tochopherol (vitamin E) reduces the cytotoxicity of 7-K by inhibiting its distribution to the lipid raft domains (Berthier et al, 2004; Royer et al, 2009).…”
Section: The Involvement Of Oxysterols In Ad Pathogenesismentioning
confidence: 99%
“…Ghelli et al [89] showed that in ECV304 cells treated with 7-KC no cytochrome c release was associated with the observed loss of cell viability. More mechanistic insight has been gained from recent studies: Kim and Lee [90] provided evidence that the tyrosine kinase inhibitor AG126 reduced 7-KC-induced cell death by suppressing mitochondrial permeability change, apparently via inhibition of ROS generation and GSH (glutathione) depletion. On the other hand, Gao et al [91] demonstrated that apoptosis of J774 macrophage induced by the oxysterol cholesterol secoaldehyde (3β-hydroxy-5-oxo-5,6-secocholestan-6-al) is mediated via the mitochondrial pathway but without involvement of ROS.…”
Section: Oxysterol-induced Cell Deathmentioning
confidence: 99%
“…Recently, preventive effects of AG126 in 7-ketocholesterol (KCL) toxicity were investigated in relation to the mitochondria-mediated cell death process by Kim and Lee (2010). They could show that AG126 attenuated the 7-KCL-induced decrease in cytosolic Bid and Bcl-2 levels and that it increased cytosolic pro-apoptotic Bax levels.…”
Section: Ag126 and Mitochondriamentioning
confidence: 99%